Coverage of gender violence against women in two Argentine newspapers. A comparison with the Colombian case - Enrique Ordóñez, Jairo (2020)
This proposal constitutes the third phase of an investigation on the communication-gender relationship, which this time was based on a media observation on women and gender violence, which is the subject of. It was sought to test 8 of the 13 categories found in the Colombian case in the first phase (Ordóñez et al., 2016a) and establish whether they are replicated in the Argentine national press. We also sought to identify new emerging categories that, in the same way, justify, validate or minimize gender violence against women. The year of observation was 2018 and was based on a quantitative approach that allowed us to conclude that the categories detected in the Colombian press are present in the Argentine press, although to a lesser extent than in Colombia. New categories were also detected (such as the “Exaltation of Sexual Violence”, as if the important thing was the violence of this type and not the homicide itself).